The Importance of Animal and Marine Fat in the Faroese Cuisine: The Past, Present, and Future of Local Food Knowledge in an Island Society - Svanberg, Ingvar (Frontiers in Sustainable Food Systems, 2021)
Since ecological and climatic conditions limit the possibilities for cereal production, the old-established Faroese traditional food system is principally based on the utilization of animal protein and fat. The diet of the islanders has thus been adapted to the specific environmental circumstances of the area. Historically, fat has provided a high energy and nutritious food source for the hard-working sheep farmers and fishermen. Fat procured from both land and marine animals has formed a vital part of the local food culture. Apart from the insubstantial amount of butter produced in the Faroe Islands, tallow from sheep, fish fat and liver from codfishes, and the blubber from the long-finned pilot whale, has been widely utilized within the households. During the last century, Faroese diet has changed due to external factors such as closer integration into the world economy, modernization, and improved household economy. Although butter, cheese and other dairy products as well as margarine and vegetable oil are nowadays readily available in the convenience shops and supermarkets, tallow, and whale blubber continue to be part and parcel of many of the islanders' cuisine. Today, however, such products are not primarily consumed for their energy content. Instead, it can be seen as a contemporary and regional expression of appraisal toward Faroese cuisine. Appreciating and consuming local food has become an important part of expressing Faroese cultural identity. The traditional diet therefore links the islanders with their history. However, the preparation of Faroese food products is highly dependent on traditional knowledge of how to extract different types of animal fat and process it into locally made dishes. Thus, the long-term survival of traditional Faroese gastronomy is contingent on the maintenance and continuation of this knowledge.